PEMENUHAN HAK ANAK ATAS KESEHATAN DI PROVINSI NANGGROE ACEH DARUSSALAM DI DASARKAN QANUN ACEH NOMOR 11 TAHUN 2008 TENTANG PERLINDUNGAN ANAK - Kurniawan, Andri (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Qanun Aceh No. 11 of 2008 concerning Protection of Children is based on the perspective that protection of children in all aspects is a part of the development activities and distinctive peculiarities of Aceh and promoting community life and nation in the Republic of Indonesia. Obligation to provide protection to children based on the principles of non-discrimination, the best interests of the child, right to life, survival, and development, and reward for the opinions of children. In the implementation, legal protection of children in Nanggroe Aceh Darussalam not fully comply. Those constraint relating with the legislation, the body builder, body organizer, health facilities and membership. Keywords : Qanun, Protection of the Child, Rights of the Child on Health